115 Early vs Late Gamma Knife Radiosurgery Following Transsphenoidal Resection for Nonfunctioning Pituitary Macroadenomas: A Matched Cohort Study. (August 2015) - Pomeraniec, Isaac Jonathan; Dallapiazza, Robert; Xu, Zhiyuan; Jane, John; Sheehan, Jason P.
Abstract : INTRODUCTION: Nonfunctioning pituitary macroadenomas frequently invade the cavernous sinus and many cannot be completely resected without undue risk. Gamma knife radiosurgery (GKRS) is highly effective for treating residual and recurrent adenomas. However, there is no consensus as to whether GKRS should be used early to treat residual adenoma or after a set period of clinical observation during which adenoma growth is demonstrated. Given the high incidence of adenoma progression after subtotal resection over time, the present study examines the potential utility of GKRS performed shortly after transsphenoidal surgery vs expectant management with delayed GKRS treatment. METHODS: This is a retrospective review of patients with nonfunctioning pituitary macroadenomas who underwent transsphenoidal surgery followed by GKRS from 1996 to 2013 at the University of Virginia. Patients were stratified based on the interval between resection and radiosurgery. Operative results, imaging, and clinical outcomes were compared across groups following early (<6 months) or late (>6 months) radiosurgery. RESULTS: Sixty-four patients met our study criteria and were grouped based on early (n = 32) or late (n = 32) GKRS following transsphenoidal resection. There was greater risk of adenoma progression after GKRS in the late radiosurgical group ( P = .027) over a median radiographic follow-up period of 68.5 months. Furthermore, there was a significantly higher occurrence of post-GKRS endocrinopathy in the late radiosurgical cohort ( P = .041). Seventeen percent of patients without endocrinopathy in the early cohort developed new endocrinopathies following radiosurgery vs 64% in the late cohort ( P = .036). This difference was secondary to a significantly higher rate of adenoma growth during the observation period in the late treatment cohort ( P = .014). CONCLUSION: Early treatment with GKRS appears to decrease the rate of radiographic and symptomatic progression of subtotally resected nonfunctioning pituitary macroadenomas compared with late GKRS treatment after a period of expectant management. Delaying radiosurgery may place patients at increased risk for adenoma progression and endocrinopathy.